The effect of oxytocin receptor blockade on parturition in guinea pigs. - Schellenberg, J C (1995)
The mechanism of the onset of labor is unknown in humans and guinea pigs. Contrary to most other species, progesterone withdrawal appears not to precede the onset of labor. To elucidate the role of oxytocin in the onset and maintenance of labor, guinea pigs were fitted with vascular catheters, an intraabdominal pressure catheter and an array of uterine electromyogram electrodes. An oxytocin antagonist (des-Gly9-[D-Trp2,Thr4,Orn8]dC6-oxytocin, 20 micrograms/kg per h, n = 11) or saline solution (n = 12) was infused starting on day 66 of gestation (term is 69 d). Oxytocin receptor blockade resulted in decreased uterine activity and a prolonged expulsive phase (second stage) of labor. Fetal delivery was delayed and fetal mortality was increased. The onset of the expulsive phase of labor was delayed but maximum uterine activity occurred in time together with a timely change in uterine electromyogram activity from a prepartum to a postpartum pattern following an unaltered progressive increase in baseline uterine activity. This indicates that oxytocin is requisite for the normal progress of the first and second stage of labor, but has no involvement in the mechanism of the onset and the timing of labor.